Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

A novel inversion method for assessing pipe corrosion condition based on upstream-downstream water quality variation in drinking water distribution systems - Yun-Qiao Zeng; Tian-Yang Zhang; Zhen-Ning Luo; Ling Hu; Bing Geng; Renjie Pan; Zhu Peng; Dai-Xu Zhang; Yi-Ru Chen; Huan He; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Uranium in-situ leaching: Combining conditional deep convolutional generative adversarial network (cDC-GAN) and ensemble smoother with multiple data assimilation (ES-MDA) to estimate the heterogeneous permeability coefficient field - Wen-gui Ji; Yue Luo; Bing Wang; Yi-ru Zhou; Yan-hong Zhang; Xian-ping Luo (Hydrometallurgy, 2026)

Non-nutritive sweeteners in hand-shaken beverages: Occurrence, consumption patterns, and dietary risk assessment - Yu-Chia Yeh; Wan-Ru Li; Yu-Syuan Luo (Food Research International, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Shape-memory effect in a flexible hydrogen-bonded organic framework for efficient C2H2/CO2 separation - Chunchen Gao; He Zheng; Wenjie Chen; Yiting Guo; Ru Xu; Ziyi Luo; Qifeng Luo; Xingliang Nie; Xin Lian; Xiongli Liu; Yabing He; Lin Li; et al. (Chemical Engineering Journal, 2026)

Mechanical degradation mechanisms of colorful clay subjected to dry-wet cycling - Yin-Lei Sun; Qing-Ru Du; Xin-Yao Yang; Wei Luo; Xiang Qian; Xian-Wei Zhang (Transportation Geotechnics, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Divergent responses of soil respiration to reduced rainfall amount and frequency, and to nitrogen fertilization in a typical steppe - Lan Du; Yan Shen; Jiatao Zhang; Yonghong Luo; Jinbao Zhang; Ru Tian; Zhuwen Xu (Journal of Environmental Management, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

The OsMYB60–OsGL1-11 module regulates drought tolerance in rice - Ru Li; Jinliang Sun; Fuping Chen; Xuemei Qin; Tianmin Ouyang; Weijian Cen; Jijing Luo (Plant Science, 2026)

Ratio limitation of burnt-bitter-aroma compounds in strong-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Zheng-Juan Zhu; Jing Luo; Ling Xiang; Yan-Hong Xiang; Song-Tao Wang; Wen-Wen Zhang; Qing-Qing Liu; Ting Huang; Zheng-Hong Xu; Yong-Jun Yuan (Food Chemistry, 2026)

Quantifying summer land surface cooling performance of parks and population accessibility across urban–rural gradients in subtropical megaregions - Qianyi Bei; Wenzhuo Luo; Xinyin Li; Jiangdi Ru; Siyu Zhou; Jing Xie (Building and Environment, 2026)

Size-dependent shear behavior of backfill–rock interfaces constructed from in-situ 3D morphology: experimental and numerical study - Wenkai Ru; Diyuan Li; Hiroyuki Noda; Hao Gong; Pingkuang Luo; Jinyin Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

New fossil moths (Lepidoptera: Micropterigidae) in middle Cretaceous Kachin amber from Myanmar - Ning Han; Xin-Ru Luo; Jia-Jia Wang; Chungkun Shih; Wei-Ting Zhang; Dong Ren (Palaeoworld, 2026)

A cyclic nucleotide-gated channel gene HcCNGC11 positively regulates salt stress responses in kenaf (Hibiscus cannabinus L.) - Jiao Yue; Canni Chen; Qiuping Wang; Rehmat Ullah; Yuqi Tan; Xu Wang; Huaming Lu; Dengjie Luo; Ru Li; Tao Chen; Peng Chen (Plant Molecular Biology, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

3D Morphology Analysis and Shear Strength Prediction Model for a Backfill–Rock Interface - Wenkai Ru; Diyuan Li; Zhenyu Han; Pingkuang Luo; Hao Gong (Rock Mechanics and Rock Engineering, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

Online state estimation of steam generator based on extended Kalman filter - Leilei Qiu; YuLong Wang; JiaCheng Zhang; Ru Zhang; Gang Luo; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2026)

Experimental study on the enhanced separation performance of a vertical corrugated plate dryer under acoustic agglomeration - Tuo Wang; Siqin Hou; Mingyang Sun; Zerun Zhang; Pei Luo; Lei Jiang; Ru Li; Guoqing Shen; Rulei Sun (Annals of Nuclear Energy, 2026)

OsPP2C03 positively regulates rice drought stress resistance through a non-canonical ABA pathway - Yao Wang; Mingxin Chen; Di Wu; Ru Li; Hanxing Wei; Lingwen Meng; Xuemei Qin; Jinliang Sun; Tianmin Ouyang; Weijian Cen; Rongbai Li; Jijing Luo (Plant Science, 2026)

A non-specific lipid transfer protein gene HcnsLTP111 positively regulates drought and salt stress tolerance in kenaf (Hibiscus cannabinus L.) - Dengjie Luo; Rehmat Ullah; Renxue Li; Benxian Li; Caijin Wang; Jiao Yue; Jiao Pan; Huaming Lu; Yun Li; Gang Jin; Ru Li; Tao Chen; et al. (Phytochemistry, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

A Review of Envelope Inversion for Large-Scale Background Model Building - Yong Hu; Ru-Shan Wu; Jingrui Luo; Guoxin Chen (Surveys in Geophysics, 2025)

GNF-5837 attenuates acute liver injury by inhibiting oxidative stress - Xinru Zhou; Xianyu Luo; Qian Huang; Yi Ru; Didi Liu; Maoyuan Linghu; Yi Huang (Molecular Biology Reports, 2025)

Impact of vancomycin and Clostridioides difficile on the secretome and pathogenicity of Clostridium innocuum - Yi-Ywan M. Chen; Kun-Yi Chien; Hui-Ru Shieh; Cai-Jie Luo; Yu-Xun Chang; Chuan Chiang-Ni; Chih-Ho Lai; Cheng-Hsun Chiu (Medical Microbiology and Immunology, 2025)

Gut microbiome-targeted therapeutics for chronic kidney disease: comparative efficacy of probiotic and microbial preparations - Yi-Ke Li; Wen-Ru Li; Huan Ren; Chen-Lin Xiao; Zhen Guo; Jian-Quan Luo (Inflammopharmacology, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

The cotton gene family encoding translationally controlled tumor proteins and the role of GhTCTP5 in salt tolerance - Bo Pang; Jialin Chen; Ping Luo; Ru Zhang; Jing Li; Weiwei Liang; Wenwei Gao; Shengmei Li (Plant Science, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

G1-mediated OsMADS1 repression regulates sterile lemma development in rice - Xuemei Qin; Jinliang Sun; Ru Li; Weijian Cen; Rongbai Li; Jijing Luo (Plant Cell Reports, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Integrative transcriptome and metabolome analyses provide insights into rice defence against Chilo suppressalis oviposition - Chen Shen; Haibo Bao; Zhengping Yu; Xiaoyan Cang; Ru Zhang; Junxian Song; Guanghua Luo; Jichao Fang (Plant Molecular Biology, 2025)

The Astrocyte: A New Component of The Engram Regulates Memory Recall - Ru Li; Zilan Luo; Ding Zhong; Xia Deng; Liang Gao (Neuroscience Bulletin, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

How do different ant species mediate CH4 fluxes in slash-burn tropical forest soils? - Lingling Xie; Shaojun Wang; Mei Lu; Bo Xiao; Zhengjun Wang; Zhipeng Guo; Xiaofei Guo; Shuang Luo; Ru Li; Jiahui Xia; Shengqiu Yang; Mengjie Lan (Soil and Tillage Research, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Correction: Ecological Environmental Changes and the Impact on Alpine Wetland Spatiotemporal Differentiation in Western Sichuan - Haijun Wang; Xiangdong Kong; Cuicui Jiao; Hu Li; Minghong Peng; Ji Luo; Onanong Phewnil; Ru Xue (Wetlands, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

TBBPA caused multiple intestinal injuries via ROS/NF-κB signal in common carp - Man Qian; Yuan Geng; Jing-jing Wang; Hong-ru Wang; Ji-long Luo; Xue-jiao Gao (Aquatic Toxicology, 2025)

Ecological Environmental Changes and the Impact on Alpine Wetland Spatiotemporal Differentiation in Western Sichuan - Haijun Wang; Xiangdong Kong; Cuicui Jiao; Hu Li; Minghong Peng; Ji Luo; Onanong Phewnil; Ru Xue (Wetlands, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Quantitative estimation of three-dimensional fracture density: Insights from the stereological relationship between borehole and universal elliptical DFN - Kun Xiao; Ru Zhang; Li Ren; Anlin Zhang; Jing Xie; Ziwen Luo; Zetian Zhang; Chendi Lou; Zeqian Yang (Engineering Geology, 2025)

Nitrogen addition alleviates the negative effects of reduction in precipitation on soil multifunctionality in a typical steppe - Yan Shen; Yonghong Luo; Lan Du; Ru Tian; Wenqian Shao; Jiatao Zhang; Na Li; Jinbao Zhang; Shan Wang; Mohsin Mahmood; Zhuwen Xu (Applied Soil Ecology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Hard rock fragmentation by dynamic conical pick indentation under confining pressure - Pingkuang Luo; Diyuan Li; Wenkai Ru; Hao Gong; Mimi Wang (International Journal of Rock Mechanics and Mining Sciences, 2024)

Understanding the evolution of molybdenum-nitrogen doped carbon with long-term durability for efficient oxygen reduction reaction - Xingyu Luo; Bingbao Mei; Ru Feng; Xiaofeng Xu; Zhongyan Zhang; Mingyu Ou; Fanfei Sun; Huajun Zheng; Meiqin Shi (Chemical Engineering Journal, 2024)

Seed priming using different agents can alleviate salt stress in kenaf (Hibiscus cannabinus L.) by activating antioxidant system and related genes expression - Renxue Li; Dengjie Luo; Muzammal Rehman; Xin Li; Caijin Wang; Shan Cao; Guofeng Xu; Meng Wang; Canni Chen; Jingzhi Nie; Ru Li; Tao Chen; et al. (Physiology and Molecular Biology of Plants, 2024)

Drought and nitrogen deposition regulate plant nutrient resorption in a typical steppe - Yonghong Luo; Yan Shen; Ahmed Salah Elrys; Lan Du; Mohsin Mahmood; Jiatao Zhang; Haiyan Ren; Jinbao Zhang; Na Li; Ru Tian; Wenqian Shao; Ahmed S.M. Elnahal; et al. (Agriculture, Ecosystems & Environment, 2024)

Effects of 3-year organic farming management on soil antibiotic resistant genes and virulence factors in a double rice cropping system - Shao-Yi Ruan; Hao-Wen Luo; Xiang-Ru Tang; Jian-Ying Qi (Science of The Total Environment, 2024)

The irregular developmental duration mainly caused by the broad-complex in Chilo suppressalis - Zhi-Ling Zhang; Qing-Yu Xu; Ru Zhang; Chen Shen; Hai-Bo Bao; Guang-Hua Luo; Ji-Chao Fang (Pesticide Biochemistry and Physiology, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Supramolecular assembly of dual crosslinked nanocomposite polysaccharides hydrogel: Integration of injectable, self-healing, and pH-responsive platform for sustained delivery of polyphenols - Fatima-ezzahra Ettoumi; Hao Huang; Yanqun Xu; Lei Wang; Qiaomei Ru; Yichen Hu; Liang Zou; Zisheng Luo (Food Hydrocolloids, 2024)

A new approach for 3D structure characterization of rock mass using an improved elliptical discrete fracture network model - Ziwen Luo; Ru Zhang; Jing Xie; Kun Xiao; Li Ren; Zetian Zhang; Xinzhong Wang; Anlin Zhang (Engineering Geology, 2024)

Performance evaluation of vegetation concrete with carbonaceous mudstone aggregates in slope protection under wet-dry conditions - Ling Zeng; Jin-Tao Luo; Zi-Ru Yang; Hui-Cong Yu; Wei Wen; Qian-Feng Gao; Hong-Ri Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Novel pyrrolidine-alkylamino-substituted dicyanoisophorone derivatives as near-infrared fluorescence probe for imaging β-amyloid in vitro and in vivo - Hui Zhou; Jihang Zhai; Huiyuan Gong; Ru Fang; Yongmei Zhao; Wen Luo (Analytica Chimica Acta, 2024)

Author Correction: Multiscale nest-site selection and breeding biology: infrared camera monitoring of the great crested grebe Podiceps cristatus in a plateau freshwater lake in southwestern China - Zu K. Luo; Xian H. Shao; Yu B. Liu; Ru B. Wang (Ornithology Research, 2024)

Multiscale nest-site selection and breeding biology: infrared camera monitoring of the great crested grebe Podiceps cristatus in a plateau freshwater lake in southwestern China - Zu K. Luo; Xian H. Shao; Yu B. Liu; Ru B. Wang (Ornithology Research, 2024)

Reduction in precipitation amount, precipitation events, and nitrogen addition change ecosystem carbon fluxes differently in a semi-arid grassland - Lan Du; Yonghong Luo; Jiatao Zhang; Yan Shen; Jinbao Zhang; Ru Tian; Wenqian Shao; Zhuwen Xu (Science of The Total Environment, 2024)

DNA Methylome Provide New Insights into the Physiological-Molecular Regulation of Salt Stress in Kenaf Using 5-azaC Pretreatment - Zengqiang Li; Dengjie Luo; Shan Cao; Samavia Mubeen; Muzammal Rehman; Caijin Wang; Gang Jin; Ru Li; Tao Chen; Peng Chen (Journal of Soil Science and Plant Nutrition, 2024)

Comparative evaluation of acid-resistant nanofiltration membranes for heavy metal removal in acidic wastewater - Chun Cui; Cong Luo; Tian Tian; Ru Feng; An-Kang Li; Shi-Peng Sun; Xue-Li Cao (Desalination, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Opportunist ant species dominate metropolitan microhabitats: Evidence from the eastern margin of the Qinghai-Tibetan plateau - Ru-Yi Yin; Xin-Yu Luo; Xiang-Qin Huang; Zi-Xuan Zhao; Chris Newman; Yi Luo; Zhao-Min Zhou (Soil Biology and Biochemistry, 2024)

Construction of self-assembled nano cellulose crystals/chitosan nanobubbles composite hydrogel with improved gallic acid release property - Miral Javed; Hao Huang; Yueran Ma; Fatima-ezzahra Ettoumi; Lei Wang; Yanqun Xu; Hesham R. El-Seedi; Qiaomei Ru; Zisheng Luo (Food Chemistry, 2024)

Risk factors for short-term prognosis of end-stage liver disease complicated by invasive pulmonary aspergillosis - Weiyan Yu; Ying Xiao; Yue Luo; Yangyang Hu; Ru Ji; Wei Wang; Zhinian Wu; Zeqiang Qi; Tingyu Guo; Yadong Wang; Caiyan Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Tyrosine hydroxylase plays crucial roles in larval cuticle formation and larval-pupal tanning in the rice stem borer, Chilo suppressalis - Qing-Yu Xu; Zhi-Ling Zhang; Ru Zhang; Ary A. Hoffman; Ji-Chao Fang; Guang-Hua Luo (Pesticide Biochemistry and Physiology, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Physiological, transcriptome and gene functional analysis provide novel sights into cadmium accumulation and tolerance mechanisms in kenaf - Shan Cao; Meng Wang; Jiao Pan; Dengjie Luo; Samavia Mubeen; Caijin Wang; Jiao Yue; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Journal of Environmental Sciences, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Morpho-physio-biochemical, molecular, and phytoremedial responses of plants to red, blue, and green light: a review - Muzammal Rehman; Jiao Pan; Samavia Mubeen; Wenyue Ma; Dengjie Luo; Shan Cao; Wajid Saeed; Gang Jin; Ru Li; Tao Chen; Peng Chen (Environmental Science and Pollution Research, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Does biogas industrial policy promote the industrial transformation? - Erga Luo; Ru Yan; Yaping He; Zhen Han; Yiyu Feng; Wenrong Qian; Jinkai Li (Resources Policy, 2024)

Effects of freezing methods on physicochemical properties, protein/fat oxidation and odor characteristics of surimi gels with different cross-linking degrees - Xiaoying Luo; Kang Huang; Yongxin Niu; Xu Zhang; Yueqi An; Ru Liu; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Evaluation of light irradiation on anthocyanins and energy metabolism of grape (Vitis vinifera L.) during storage - Sanusi Shamsudeen Nassarawa; Nina Bao; Xingtao Zhang; Qiaomei Ru; Zisheng Luo (Food Chemistry, 2024)

Nitrite acts as the key “switch” governing the free nitrous acid pretreatment in anaerobic digestion: A comprehensive mechanism of abiotic, bioinformatics and bioenergetics effects - Zhibang Han; Ru Fang; Xueting Wang; Guangchen Huang; Dong Wu; Jun Tai; Bing Xie; Yinglong Su; Jingyang Luo; Gang Zhao; Ming Jiang (Chemical Engineering Journal, 2024)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Study on Creep Characteristics and Nonlinear Fractional-Order Damage Constitutive Model of Weakly Cemented Soft Rock - Wenkai Ru; Shanchao Hu; Aohui Zhou; Pingkuang Luo; Hao Gong; Chenxi Zhang; Xuedong Zhou (Rock Mechanics and Rock Engineering, 2023)

Adult Kerion Celsi Caused by Trichophyton tonsurans Secondary to Black Dot Tinea Capitis - Qian-ru Ye; Yu-wu Luo; Xin Zhou; Qing-qing Li; Yu-mei Liu (Mycopathologia, 2023)
A 34-year-old female patient presented with hair loss due to black dot tinea capitis caused by Trichophyton tonsurans for 6 months. Hair loss progressed to painful swelling for 2 months due to kerion Celsi which may be associated with treatment like topical minoxidil, antibiotic and corticosteroid previously. The patient was treated with oral Itraconazole initially without success but cured by Terbinafine eventually. It’s very interesting that the patient caught kerion celsi secondary to a four-month history of hair loss due to black dot tinea capitis.

Effects of contrasting tillage managements on the vertical distribution of plant- and microbial-derived carbon in rice paddy - Jian-Ying Qi; Xiang-Bin Yao; Mei-Yang Duan; Xiang-Wen Huang; Mei-Yi Fan; Ya Yang; Hao-Wen Luo; Xiang-Ru Tang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

Physiological and DNA methylation analysis provides epigenetic insights into kenaf cadmium tolerance heterosis - Dengjie Luo; Hai Lu; Caijin Wang; Samavia Mubeen; Shan Cao; Jiao Yue; Jiao Pan; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Plant Science, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Polysaccharides from the hard shells of Juglans regia L. modulate intestinal function and gut microbiota in vivo - Xiaoyu Li; Siying An; Zhen Luo; Peng Zhou; Lu Wang; Ru Feng (Food Chemistry, 2023)

Comparative Physiological and Transcriptomic Analysis Provide New Insights of Crucial Pathways and Genes Regulating Kenaf Salt Tolerance - Yali Hu; Zengqiang Li; Meiqiong Tang; Dengjie Luo; Muhammad Haneef Kashif; Shan Cao; Caijin Wang; Jiao Yue; Zhen Huang; Jiao Pan; Xia Wu; Qijing Wu; et al. (Journal of Plant Growth Regulation, 2023)

NOS2/miR-493-5p Signaling Regulates in the LPS-Induced Inflammatory Response in the RAW264.7 Cells - Xiaofei Li; Yongrui Yang; Nihong Lu; Feng Luo; Ru Fan; Niancai Peng (Biochemical Genetics, 2023)

Characteristics of dynamic shear modulus and damping ratio and the structural formula of EPS particles lightweight soil - Tian-shun Hou; Yi-xiang Cui; Xing-ru Pan; Ya-sheng Luo; Qian Liu (Soil Dynamics and Earthquake Engineering, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Sipunculus nudus genome provides insights into evolution of spiralian phyla and development - Yi Qi; Liang Chen; Binhua Wu; Xiaoning Tang; Xiao Zhu; Ru Li; Kefeng Wu; Hui Luo (Frontiers in Marine Science, 2023)
Introduction Sipunculus nudus is the most known species in the genus Sipunculus , distributed in tropical and subtropical coastal waters. Methods PacBio sequencing and Illumina sequencing were combined for whole-genome sequencing of S. nudus . LC-MS/MS analysis was performed for the metabolomics of S. nudus . Results Herein, we report a 1.75 Gb complete genome assembly with a contig N50 size of 450 kb of the S. nudus based on a strategy combining third-generation long-read sequencing and Illumina sequencing. A total of 80391 protein-coding genes are annotated in this genome. Furthermore, gene family evolution analysis shows that S. nudus belonged to Mollusca or was close to Mollusca , but distinct with Annelida . Transcriptome analysis indicates the involvement of complex developmental events in larve. KEGG pathway analysis of differentially expressed genes showed that these DEGs were mainly enriched in the pathway of amino acid metabolism, lipid metabolism and transport and catabolism. LC-MS/MS analysis shows that S. nudus was rich in a variety of nutritional and functional components, such as carnitine, free amino acids, unsaturated fatty acids, inosine and methionine sulfoxide. Combined transcriptome with LC-MS/MS analysis, the results showed that gene expression and metabolic level involved in the inosine, arginine and proline biosynthesis of S. nudus during different growth stages were significantly changed. Discussion Our genome assembly provides an important genome resource and new insight into the relationships of Sipuncula to other spiralian phyla. Meanwhile, transcriptome and LC-MS/MS analysis reveal the systematic gene expression profiles and metabolite components of S. nudus during different growth stages, which provide new insight into the exploration and development of bioactive molecules of S. nudus .

Lycopsid Lepacyclotes Emmons from the Middle Triassic of the Ordos Basin, North China and reviews of the genus - Shenghui Deng; Yuanzheng Lu; Ru Fan; Zhong Luo; Xueying Ma; Dan Lyu; Yanqi Sun (Review of Palaeobotany and Palynology, 2023)

Dissolved organic matter–assisted phytoremediation potential of cotton for Cd-contaminated soil: a relationship between dosage and phytoremediation efficiency - Tao Min; Tong Luo; Hao He; Jie Qin; Yan Wang; Liyang Cheng; Sibo Ru; Junhua Li (Environmental Science and Pollution Research, 2022)

The Effects of Acidic Compost Tea on Activation of Phosphorus, Fe, Zn, and Mn in Calcareous Soil and Cotton (Gossypium hirsutum L.) Growth in Xinjiang, China - Tong Luo; Weidan Lu; Lili Chen; Tao Min; Sibo Ru; Changzhou Wei; Junhua Li (Journal of Soil Science and Plant Nutrition, 2022)

NNMT is induced dynamically during beige adipogenesis in adipose tissues depot-specific manner - Ru Jia; Xiaojing Wei; Jianan Jiang; Zhao Yang; Jiaqi Huang; Jing Liu; Jianqun Yan; Xiao Luo (Journal of Physiology and Biochemistry, 2022)

Epigenetics in psoriasis: perspective of DNA methylation - Ying Luo; Keshen Qu; Le Kuai; Yi Ru; Keke Huang; Xiaoning Yan; Meng Xing (Molecular Genetics and Genomics, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

An Infrared Touch System for Automatic Behavior Monitoring - Qingqing Liu; Xing Yang; Ru Song; Junying Su; Moxuan Luo; Jinling Zhong; Liping Wang (Neuroscience Bulletin, 2021)
Key requirements of successful animal behavior research in the laboratory are robustness, objectivity, and high throughput, which apply to both the recording and analysis of behavior. Many automatic methods of monitoring animal behavior meet these requirements. However, they usually depend on high-performing hardware and sophisticated software, which may be expensive. Here, we describe an automatic infrared behavior-monitor (AIBM) system based on an infrared touchscreen frame. Using this, animal positions can be recorded and used for further behavioral analysis by any PC supporting touch events. This system detects animal behavior in real time and gives closed-loop feedback using relatively low computing resources and simple algorithms. The AIBM system automatically records and analyzes multiple types of animal behavior in a highly efficient, unbiased, and low-cost manner.

A comprehensive integrated transcriptome and metabolome analyses to reveal key genes and essential metabolic pathways involved in CMS in kenaf - Meiqiong Tang; Zengqiang Li; Dengjie Luo; Fan Wei; Muhammad Haneef Kashif; Hai Lu; Yali Hu; Jiao Yue; Zhen Huang; Wenye Tan; Ru Li; Peng Chen (Plant Cell Reports, 2021)

Early-Life Multiple Sevoflurane Exposures Alleviate Long-term Anxiety-Like Behaviors in Mice via the proBDNF/ERK Pathway - Ru-Yi Luo; Cong Luo; Feng Zhong; Wei-Yun Shen; Hui Li; Yan-Ling Zhang; Ru-Ping Dai (Molecular Neurobiology, 2021)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

A new multi-scale signed direct envelope inversion with more accurate amplitude polarity information - Jingrui Luo; Guoxin Chen; Ru-Shan Wu; Lu Wang (Acta Geophysica, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Use of discrete choice experiments to facilitate design of effective environmentally friendly agricultural policies - Na-na Wang; Liang-guo Luo; Ya-ru Pan; Xue-mei Ni (Environment, Development and Sustainability, 2019)

The transcription factor MYB15 is essential for basal immunity (PTI) in Chinese wild grape - Yangyang Luo; Ru Bai; Jing Li; Weidong Yang; Ruixiang Li; Qingyang Wang; Guifang Zhao; Dong Duan (Planta, 2019)

A specific allele of MYB14 in grapevine correlates with high stilbene inducibility triggered by Al3+ and UV-C radiation - Ru Bai; Yangyang Luo; Lixin Wang; Jing Li; Kerun Wu; Guifang Zhao; Dong Duan (Plant Cell Reports, 2019)

Velocity and Density Reconstruction Based on Scattering Angle Separation - Jingrui Luo; Ru-Shan Wu (Pure and Applied Geophysics, 2018)

Characterisation of silver release from nanoparticle-treated baby products - Ru Ding; Pingjian Yang; Yuan Yang; Zhaoguang Yang; Li Luo; Haipu Li; Qiang Wang (Food Additives & Contaminants: Part A, 2018)

Subdivision and age of the Yanchang Formation and the Middle/Upper Triassic boundary in Ordos Basin, North China - Shenghui Deng; Yuanzheng Lu; Zhong Luo; Ru Fan; Xin Li; Yi Zhao; Xueying Ma; Rukai Zhu; Jingwei Cui (Science China Earth Sciences, 2018)

An optimized fed-batch culture strategy integrated with a one-step fermentation improves l-lactic acid production by Rhizopus oryzae - Yongqian Fu; Xiaolong Sun; Huayue Zhu; Ru Jiang; Xi Luo; Longfei Yin (World Journal of Microbiology and Biotechnology, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

Sex-Dependent Glial Signaling in Pathological Pain: Distinct Roles of Spinal Microglia and Astrocytes - Gang Chen; Xin Luo; M. Yawar Qadri; Temugin Berta; Ru-Rong Ji (Neuroscience Bulletin, 2018)

Spinal CCL2 Promotes Central Sensitization, Long-Term Potentiation, and Inflammatory Pain via CCR2: Further Insights into Molecular, Synaptic, and Cellular Mechanisms - Rou-Gang Xie; Yong-Jing Gao; Chul-Kyu Park; Ning Lu; Ceng Luo; Wen-Ting Wang; Sheng-Xi Wu; Ru-Rong Ji (Neuroscience Bulletin, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Enhancement of ginsenoside Rg1 in Panax ginseng hairy root by overexpressing the α-l-rhamnosidase gene from Bifidobacterium breve - Ru Zhang; Bian-Ling Zhang; Gu-Cai Li; Tao Xie; Teng Hu; Zhi-Yong Luo (Biotechnology Letters, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Biochemical Properties and Stability of Antioxidative Activity of Half-Fin Anchovy ( Setipinna taty ) Fermented Product - Ru Song; Rongbian Wei; Hongyu Luo (Journal of Aquatic Food Product Technology, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Isolation and characterization of a novel PDR-type ABC transporter gene PgPDR3 from Panax ginseng C.A. Meyer induced by methyl jasmonate - Ru Zhang; Jingjia Huang; Jie Zhu; Xiaolei Xie; Qin Tang; Xianghui Chen; Jun Luo; Zhiyong Luo (Molecular Biology Reports, 2013)

Expression of tyrosine kinase receptor C in the segments of the spinal cord and the cerebral cortex after cord transection in adult rats - Dong-Xiang Qian; Hong-Tian Zhang; Ying-Qian Cai; Peng Luo; Ru-Xiang Xu (Neuroscience Bulletin, 2011)

Differentiation of cryopreserved human umbilical cord blood-derived stromal cells into cells with an oligodendrocyte phenotype - Yong-Chun Luo; Hong-Tian Zhang; Hao-Yu Cheng; Zhi-Jun Yang; Yi-Wu Dai; Ru-Xiang Xu (In Vitro Cellular & Developmental Biology - Animal, 2010)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)